2013
DOI: 10.5230/jgc.2013.13.3.164
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopy Assisted versus Open Distal Gastrectomy with D2 Lymph Node Dissection for Advanced Gastric Cancer: Design and Rationale of a Phase II Randomized Controlled Multicenter Trial (COACT 1001)

Abstract: PurposeLaparoscopy-assisted distal gastrectomy for early gastric cancer has gained acceptance and popularity worldwide. However, laparoscopy-assisted distal gastrectomy for advanced gastric cancer is still controversial. Therefore, we propose this prospective randomized controlled multi-center trial in order to evaluate the safety and feasibility of laparoscopy assisted D2-gastrectomy for advanced stage gastric cancer.Materials and MethodsPatients undergoing distal gastrectomy for advanced gastric cancer stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 25 publications
4
20
1
Order By: Relevance
“…Among the less invasive operations noted in recent years, laparoscopic gastrectomy for gastric cancer has become popular due to advances in surgical techniques. As experience with LG for early gastric cancer has accumulated, some centers have attempted to expand the indication of LG to AGC, and a few studies have already demonstrated that surgeons can safely perform laparoscopic gastrectomy in these cases and that the patients had less postoperative pain, faster recoveries, shorter hospital stays, and better qualities of life than those who underwent conventional open surgery [20,21]. Unfortunately, the majority of studies conducted on laparoscopic gastrectomy have been confined to the outcomes of LDG, and thus, LTG has not been adequately addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Among the less invasive operations noted in recent years, laparoscopic gastrectomy for gastric cancer has become popular due to advances in surgical techniques. As experience with LG for early gastric cancer has accumulated, some centers have attempted to expand the indication of LG to AGC, and a few studies have already demonstrated that surgeons can safely perform laparoscopic gastrectomy in these cases and that the patients had less postoperative pain, faster recoveries, shorter hospital stays, and better qualities of life than those who underwent conventional open surgery [20,21]. Unfortunately, the majority of studies conducted on laparoscopic gastrectomy have been confined to the outcomes of LDG, and thus, LTG has not been adequately addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Among the remaining articles, 19 studies [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] were excluded because EGC cases were mixed with AGCs in the cohort studies and data on AGCs were not extractable. Eight studies were further deleted for the following reasons: 2 studies were ongoing randomized controlled trials (RCTs) that only described study design and patient enrollment criteria without results reported [56,57]; 2 studies had overlapped enrollments with former research [58,59]; 1 study reported incomplete data that were not suitable for analysis [60]; and 3 studies discussed other issues irrelevant to the topic of this meta-analysis [61][62][63]. Finally, a total of 26 studies that compared the short-term and/or long-term results of AGCs treated by LG with those of OG were included .…”
Section: Resultsmentioning
confidence: 99%
“…Laparoscopic gastrectomy has long been used to treat EGC, and in the past decade, attention has been paid to the feasibility and safety of LG for AGC. Although several clinical trials have been initiated to evaluate the effectiveness of LG [9,10,56,57], currently we do not have enough evidence to support this surgical procedure in AGC management. To this end, we conducted this meta-analysis trying to find some clues.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the non-compliance rate of clearing the defined N2 area was selected by the authors as the most important factor for the technical feasibility of the laparoscopic procedureapproach. This study is underway and the first results will offer promising and exciting evidence of the oncologic feasibility and safety of laparoscopic-assisted distal gastrectomy for patients with advanced gastric cancer, which is the main matter of debate today in Eastern patients [34].…”
Section: Current Evidence On Laparoscopic Gastrectomy For Cancermentioning
confidence: 99%
“…As for advanced gastric cancer, a prospective randomized controlled multicenter trial in order to evaluate the safety and feasibility of laparoscopic-assisted D2 gastrectomy for advanced gastric cancer was conducted by Nam BH. et al and was published recently [34]. This study enrolled patients with distal gastrectomy for advanced gastric cancer staged by endoscopy and computed tomography.…”
Section: Current Evidence On Laparoscopic Gastrectomy For Cancermentioning
confidence: 99%